Business process improvement: A process warehouse based resource management method - Sohail, A. (Institute of Electrical and Electronics Engineers Inc., 2015)
Business process improvement is a systematic approach used by enterprises to achieve a competitive edge. A key aspect of improving the executed performance of a process is to assign the most appropriate resources to each process task. During process execution, process traces are generated which are widely acknowledged as important sources for posterior analysis. The process traces are stored in a process warehouse and it is used as a primary data source. This research is conducted to show how process warehouse based resource evaluation method (PWREM) can be used for business process improvement. The first contribution of this study is to show how information can be extracted from process warehouse based method i.e. PWREM. The second contribution of this study is to show how PWREM generated information can be used for resource management. Â© 2015 IEEE.